Resource Allocation in Post Disaster Situation using Delay Tolerant Network (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
Disaster response and recovery are very necessary in disaster management. Decision-supportsystems used in disaster management must have to deal with the complexity and uncertaintyrelated in these kinds of situations. Operational conditions, precedence conditions, resourceavailability make the resource allocation more difficult and harder. Failure to assign properhumans and proper strategies may harm the reputation of the organization. Therefore, this paperproposes a resource allocation system for such post disaster situations